1979
DOI: 10.1677/joe.0.0810183
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dna and Lecithin in Tissue Culture and Oestrogen Receptor Activity in Rat Mammary Tumours Dependent on and Independent of the Ovary

Abstract: Dimethylbenz(alpha)anthracene (DMBA)-induced and transplanted rat mammary tumours (2 lines) were examined for oestrogen receptor activity, and for sensitivity to hormones in vivo (by ovariectomy) and in vitro (by tissue culture). In vivo, the growth of all tumours induced by the administration of DMBA in random-bred Sprague-Dawley rats was found to be dependent on the ovary, whilst in all transplanted tumours (12 TG-3 and six TG-5 lines), maintained in an inbred strain of Sprague-dawley rats, growth was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…It is known that not all DMBAinduced tumours are hormone-dependent and it might be postulated that the one such tumour in which no RP could be detected might have belonged to the hormone-independent minority of DMBAinduced tumours. This study revealed no overlap in RE levels between the two groups but it should be noted that in earlier generations of the TG3 and TG5 lines higher RE concentrations were found, and the distinction between the groups was less clear-cut (Hawkins et al, 1978;Scott et al, 1979).…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…It is known that not all DMBAinduced tumours are hormone-dependent and it might be postulated that the one such tumour in which no RP could be detected might have belonged to the hormone-independent minority of DMBAinduced tumours. This study revealed no overlap in RE levels between the two groups but it should be noted that in earlier generations of the TG3 and TG5 lines higher RE concentrations were found, and the distinction between the groups was less clear-cut (Hawkins et al, 1978;Scott et al, 1979).…”
mentioning
confidence: 48%
“…Previous work in our department has shown that over 80% of such tumours regress after oophorectomy (Hawkins et al, 1978;Scott et al, 1979). Twenty-four such tumours were examined in this study.…”
mentioning
confidence: 96%
“…These were tumours induced in randombred Sprague-Dawley rats by the administration of dimethylbenz(a)anthracene (DMBA) as previously described (Hawkins, Drewitt, Freedman, Killen, Jenner & Cameron, 1976) and two lines of transplantable tumours (TG/3 and TG/5) originally derived from tumours induced by DMBA in an inbred strain of Sprague-Dawley rats (Hawkins, Hill, Freedman, Killen & Miller, 1978). At the time of study, the latter two types of tumour were ovary independent whilst more than 80% of the former tumours were ovary dependent as previously reported (Scott, Murphy & Hawkins, 1979). Tumours were harvested when approximately 1-5 1-5 cm in size, by excision of the tumour after exsanguination of the animal under ether anaesthesia.…”
Section: Rat Mammary Tumoursmentioning
confidence: 73%